Prevalence of Pneumococcal Bacteremia in Children with Sickle Cell Disease. (1st August 2013) - Patel, Ami; Zuzo, Amra; Imran, Hamayun; Siddiqui, Abdul Hafeez
Abstract : We performed a retrospective chart review of children with sickle cell disease hospitalized for fever at our local institution. We reviewed 456 hospitalizations in 133 patients between January 2006 and June 2012. The prevalence of true bacteremia was 4%. The mean C-reactive protein values and temperatures were nonsignificantly higher in patients with positive blood cultures. The mean time to detection was 22.5 hours in bacteremia compared to 32.6 hours in blood cultures that grew contaminants ( p = .034). Only two (0.4%) cases of pneumococcal bacteremia were reported and both occurred before May 2010, which marks the introduction of 13-valent pneumococcal vaccine (PCV13). Both patients with pneumococcal bacteremia had discontinued penicillin prophylaxis after the age of 5 years. The first patient was immunized but contracted a nonvaccine serotype (23B). The second patient was partially vaccinated and acquired a vaccine-preventable serotype (23F). Both serotypes were sensitive to ceftriaxone and vancomycin; one was resistant to penicillin. This is the first study reporting the prevalence of pneumococcal bacteremia since the introduction of PCV13.